Information needs of people seeking fertility services in Canada: a mixed methods analysis. Issue 1 (1st January 2021) - Lemoine, Marie-Eve; O'Connell, Siobhan Bernadette Laura; Grunberg, Paul Henry; Gagné, Karolanne; Ells, Carolyn; Zelkowitz, Phyllis
ABSTRACT: Background: Infertility is a challenging experience associated with high levels of psychological distress. Many people seeking fertility services use the internet to obtain information about their conditions and treatments. Objectives: This mixed-methods study aimed to describe the information-seeking experience of people seeking fertility services with respect to the fulfillment of their individually defined information needs and explore relationships between the fulfillment of information needs and psychological outcomes. Methods: One hundred and four participants completed a survey with close-ended and open-ended questions about their experience using an informational web-based application (app) called 'Infotility' and about their mental well-being before and after using the app. The questionnaires administered were the The Mobile Application Rating Scale (uMARS), the Fertility Quality of Life questionnaire (FertiQol), the Patient Empowerment Questionnaire (PEQ) and the General Anxiety Disorder 7-item Scale (GAD-7). Eleven participants completed in-depth qualitative interviews about their experience using the app. A thematic analysis was used to interpret qualitative results and quantitization was used to dichotomize participants into those with met information needs versus those with unmet information needs. Google Analytics was used to compare participants' reported experience with their actual use of the app. Results: The results of this study show that there is variability in the amount of information that people seeking fertility services wish to receive. Participants whose information needs were met reported improved psychological outcomes after using the app, while those with unmet needs showed no change in their psychological outcomes. Conclusions: Our results suggest that fulfilling information needs was associated with improved psychological outcomes in people seeking fertility services. Our results also suggest that individual differences in information needs should be considered when developing health educational materials.